Toll‐like receptor 8 deletion accelerates autoimmunity in a mouse model of lupus through a Toll‐like receptor 7‐dependent mechanism. Issue 1 (May 2015) - Tran, Ngoc Lan; Manzin‐Lorenzi, Céline; Santiago‐Raber, Marie‐Laure
Summary Systemic lupus erythematosus is an autoimmune disorder characterized by increased levels of lymphocyte activation, antigen presentation by dendritic cells, and the formation of autoantibodies. This leads to immune complex‐mediated glomerulonephritis. Toll‐like receptor 7 (T7) and TLR9 localize to the endosomal compartment and play important roles in the generation of autoantibodies against nuclear components, as they recognize RNA and DNA, respectively. In contrast, very little is known about endogenous TLR8 activation in mice. We therefore tested whether TLR8 could affect autoimmune responses in a murine model of lupus. We introduced a Tlr8 null mutation into C57BL/6 mice congenic for the Nba2 (NZB autoimmunity 2) locus and bearing the Yaa (Y‐linked autoimmune acceleration) mutation containing a tlr8 duplicated gene, and monitored disease development, autoantibody production, and glomerulonephritis‐associated mortality. Cellular responses were investigated in female Nba2.TLR8−/− mice bearing no copy of tlr8. The TLR8 deficiency accelerated disease progression and mortality, increased the number of circulating antibodies and activated monocytes, and heightened cellular responses to TLR7 ligation. TLR8‐deficient antigen‐presenting cells exhibited increased levels of MHC class II expression. The ability of dendritic cells to present antigens to allogeneic T cells after TLR7 ligation was also improved by TLR8 deficiency. TLR8 deletion accelerated autoimmunity in lupus‐prone mice in response to TLR7 activation. Antigen‐presenting cell function seemed to play a key role in mediating the effects of TLR8 deficiency.